Pohutu Molo'opu' Ritual Penerimaan Pemimpin Dalam Masyarakat Gorontalo - Laya, Rachmi (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
One of the oral literature which is still used in Gorontalo custom event is Tuja'i Molo'opu. Oral literature is uttered at the ceremonial of acceptance od leader in Gorontalo. As other traditions are changing, Tuja'i Molo topu also along with the changes of the society. Therefore it needs to be held as the Foundation for preservation of the study of oral literature Tuja'i Molo'opu. Thus the ceremony Tuja'i Molo'opu this is not the complement of Molo'opu ceremony, but contain a moral messages, which as ancestors messages to the man who will lead in Gorontalo. The pulpose of study is to explaine the disclosure of advice is contained in the schematic composition of the tuja'i molo'opu, and to explaine the types of advice given to the leader.The theory/used in*his-rescarch is the theory of orality Albert Bates Lord and Ruth Finnegan. Acording Finnegan oral literature contains a sequence of themes. The prominent of theme is exhortation to the leader. To apply this theory used ethnographic aproaches, to explore data on leadership message in performance as the cultural aspects of the community of Gorontalo. The data is collectected by using documentation, recording, observation and interview techniques. The results of this research show that the leadership messages included in the Tuja'i Molo 'opu as moral messages are: (1) siddiq/honest, (2) amanah/ responsible, (3) fathonah/ intelligent, (4) tabligh/ communicative.